DESCRIPTION OF PREGNANT SATISFACTION OF SERVICE PRENATAL CARE (ANC) IN BPM NY. IDA YUSNIARTI, Amd. Keb VILLAGE KEDUNGRANDU Patikraja DISTRICT DISTRICT BANYUMAS 2014 - Kartikasari B; Ikit Netra Wirakhmi; Susilo Rini (Universitas Harapan Bangsa Purwokerto, 2016)
Background : Studies of patient satisfaction need to be done in order to improve theperformance of obstetric care in case ANC best and oriented to patient satisfaction. Apreliminary survey conducted on 12 pregnant women who were conducting the examinationobtained 5 states in accordance with the services provided during the inspection because it isdone with precise and reliable, the service is polite and friendly, 3 states midwiferesponsiveness in resolving patient complaints, four people claimed services granted asexpected. Objective : to know the description satisfaction pregnant women to antenatal care providedby a midwife in the Ny BPM. Ida Yusniarti, Amd. Keb Village Kedungrandu PatikrajaDistrict of Banyumas 2014. Methods : This study used quantitative descriptive analysis with cross-sectional design, thisstudy uses primary data was acquired on August 14 to 19, 2014, with the enclosedquestionnaire (close ended) by accidental sampling technique of sampling, sample size of 30people. Result : The level of satisfaction obtained most of the pregnant women were satisfied asmuch as 16 respondents (53.3%), satisfaction levels based on the reliability of pregnantwomen said they were satisfied as much as 14 respondents (46.7%), satisfaction levels basedon the responsiveness of pregnant women said they were satisfied by 17 respondents(56.7%), satisfaction levels based on the assurance of pregnant women said they weresatisfied as much as 14 respondents (46.7%), the level of satisfaction of pregnant womenbased on empathy expressed satisfaction as much as 14 respondents (46.7%), and the level ofsatisfaction of pregnant women by tangibility menyatakanpuas as many as 15 respondents(50%). Conclusion: The satisfaction of pregnant women to antenatal care services in BPM Ny. IdaYusniarti, Amd. Keb Village Kedungrandu 2014 pregnant women found satisfaction levelslargely satisfied. Keywords : Satisfaction, pregnant women, antenatal care